Feasibility of inclusion of mustard (Brassica juncea) genotypes in intercropping and sequential cropping systems with sugarcane (Saccharum officinarum) - SHUKLA', S K; PANDEY, M B (The Indian Journal of Agricultural Sciences, 2013)
The field experiment was conducted for 2 consecutive cropping seasons (1994-96 and 1995-97) to study theeffect of different genotypes oflndian mustard [Brassica juncea (L.) Czemj & Cosson) as intercrop/sequential crop onyield and quality of sugarcane (Saccharum officinarum L.). Sole autumn cane produced highest number of millablecanes (134 500/ha), highest individual cane weight (911.6g) and sugarcane yield (82 tonnes/ha) and these weresignificantly higher compared to all the other treatments. Intercropping of different genotypes of mustard producedhigher number of millable canes, better growth, higher cane yield. cane equivalent yield, commercial cane sugarequivalent and net profit over the sequential cropping system. Juice quality was not significantly affected by thevarious intercropping/sequential cropping treatments. Intercropping of sugarcane with 'Bio 417' mustard (I : 1 row)produced highest cane equivalent yield (99.75 tonnes/ha) and net profit (Rs 50 648/ha).